Understanding atmospheric factors related to historical wildfires in southern Portugal and the impacts on tourism - Couto, Flavio (2022)
The study examines two wildfires events using high-resolution numerical modelling and complement previous studies under the Iberian Centre for Research and Forest Firefighting (CILIFO, www.cilifo.eu) framework, namely in the context of characterization of historical wildfires.